2021
DOI: 10.1108/bl-11-2020-0071
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of big data analytics management capabilities and supply chain integration on global sourcing: a survey on firm performance

Abstract: Purpose This study aims to show that management with big data analytics capability can achieve more advantages of the global sourcing process. Furthermore, this study using its conceptual attitude model aims to show that big data analytics management capability leads to an increase in firm performance by the mediating role of integration. Design/methodology/approach Using an online questionnaire, 158 managers from 13 Iranian companies taking advantage of the global sourcing process were surveyed. The validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 88 publications
1
30
0
Order By: Relevance
“…Therefore, digital technologies promote the development of internal, supplier and customer integration. As shown in prior studies, manufacturing firms’ adoption of advanced digital technologies, such as big data analysis (Razaghi & Shokouhyar, 2021 ), cloud computing (Manuel Maqueira et al, 2019 ) and the IoT (de Vass et al, 2018 ), has shown a stronger willingness to integrate internal functions and the supply chain, and their actual level of suppliers, customers and internal integration is also higher.…”
Section: Hypothesis Developmentmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, digital technologies promote the development of internal, supplier and customer integration. As shown in prior studies, manufacturing firms’ adoption of advanced digital technologies, such as big data analysis (Razaghi & Shokouhyar, 2021 ), cloud computing (Manuel Maqueira et al, 2019 ) and the IoT (de Vass et al, 2018 ), has shown a stronger willingness to integrate internal functions and the supply chain, and their actual level of suppliers, customers and internal integration is also higher.…”
Section: Hypothesis Developmentmentioning
confidence: 90%
“…For instance, the IoT has been found to render firms more proficient in data collection and information sharing, thus enhancing their supply chain integration ability (de Vass et al, 2018 ). Big data analytics have also been found to positively affect the level of supply chain integration by providing greater transparency of supply chain processes, completing responsibilities for different tasks in the organization, and improving organizational relationships and working relationships (Razaghi & Shokouhyar, 2021 ). In summary, digital-based supply chain integration helps to realize relational integration and structural integration, which are of great significance for integrated operations management (Lee, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the reviewed articles develop and empirically test research models that combine business analytics capability with different valuable, rare, and difficult to imitate resources and capabilities, which have theoretically significant roles in translating business analytics into improved firm performance. For instance, recent research highlights the complementary roles of dynamic capabilities (e.g., Wamba et al, 2017;Mikalef et al, 2020), business strategy alignment (Akter et al, 2016;Wamba et al, 2019), organizational culture (Behl, 2020;Upadhyay and Kumar, 2020), information technology capital, educated workers, high flow-efficiency production workplaces (Brynjolfsson et al, 2021), knowledge management (Ferraris et al, 2019, Shabbir andGardezi, 2020), ambidexterity (Božič and Dimovski, 2019;Rialti et al, 2019;Aljumah et al, 2021), big data analytics management capabilities (Razaghi and Shokouhyar, 2021), and resource orchestration and circular economy implementation (Kristoffersen et al, 2021). In addition, business analytics positively influences firm performance through mediating outputs, such as informational benefits (Asadi Someh and Shanks, 2015), information quality (Ashrafi et al, 2019), technological innovation (Saleem et al, 2019), product and process innovation (Saleem et al, 2020), dual innovations (Su et al, 2020), sustainable product development (Ali et al, 2020), business process performance (Aydiner et al, 2019), business decision making (Chatterjee et al, 2021), and functional performance (Torres et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…First, we propose that BDAC positively affects green supplier integration. By integrating suppliers into green practices, the focal firm may suffer different challenges such as choosing between different suppliers, incompatible goals and aspirations and inter-organizational conflict, which add complexity and uncertainty in green supplier integration (Cai et al ., 2020; Razaghi and Shokouhyar, 2021). According to OIPT, building BDAC enables the focal firm to gather and process green-related information collected from its suppliers and to improve the quality of environmental information sharing (Cai et al ., 2020; Razaghi and Shokouhyar, 2021), which may effectively diminish the risks and challenges of uncertainties and information asymmetry.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%